Ceremonial speech – graduation ceremony June 15, 2017 /Zahvalni govor – podelitev diplom 15. 6. 2017 - Pribožič, Lucija (Acta Medico-Biotechnica, 2021)
Man reaps the reward when he follows his deepest intention. As graduates, we have been growing and developing over the years with the motivation to reach a day such as this one. We have dreamed that, after years of putting much effort and time into our studies, a door to a new world will be opened to us, so we shall be able to help people on their path to health using the knowledge and skills that we have acquired. Therefore, we are finally here today in front of the door and we are waiting to open it slowly before crossing over the threshold at doctors' surgeries, health centers, hospitals and clinics. Each one of us, in our own way, is following our dreams.